Cost-effectiveness of emergency versus delayed laparoscopic cholecystectomy for acute gallbladder pathology. Issue 1 (20th October 2016) - Sutton, A J; Vohra, R S; Hollyman, M; Marriott, P J; Buja, A; Alderson, D; Pasquali, S; Griffiths, E A; Vohra, R S; Spreadborough, P; Marriott, P J; Kirkham, A; et al.
Abstract: Background: The optimal timing of cholecystectomy for patients admitted with acute gallbladder pathology is unclear. Some studies have shown that emergency cholecystectomy during the index admission can reduce length of hospital stay with similar rates of conversion to open surgery, complications and mortality compared with a 'delayed' operation following discharge. Others have reported that cholecystectomy during the index acute admission results in higher morbidity, extended length of stay and increased costs. This study examined the cost-effectiveness of emergency versus delayed cholecystectomy for acute benign gallbladder disease. Methods: Using data from a prospective population-based cohort study examining the outcomes of cholecystectomy in the UK and Ireland, a model-based cost–utility analysis was conducted from the perspective of the UK National Health Service, with a 1-year time horizon for costs and outcomes. Probabilistic sensitivity analysis was used to investigate the impact of parameter uncertainty on the results obtained from the model. Results: Emergency cholecystectomy was found to be less costly (£4570 versus £4720; €5484 versus €5664) and more effective (0·8868 versus 0·8662 QALYs) than delayed cholecystectomy. Probabilistic sensitivity analysis showed that the emergency strategy is more than 60 per cent likely to be cost-effective across willingness-to-pay values for the QALY from £0 to £100 000 (€0–120 000). Conclusion: Emergency cholecystectomy is less costly and more effective than delayed cholecystectomy. This approach is likely to be beneficial to patients in terms of improved health outcomes and to the healthcare provider owing to the reduced costs. Abstract : Emergency cholecystectomy is cheaper and more effective